The Effect of Work Motivation and Employee Performance: A Systematic Literature Review - Tamam, Moh Badrut; Sopiah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This This study aims to synthesize literature data that discusses work motivation and employee performance. Methodology/approach – A This research was prepared using PRISMA method (Prefered Reporting Item for Systematic Review and Meta-Analysis) from research related to work motivation to employee performance. The data collection method in this study used the PICO (Population, Intervention, Comparison, and Outcome) method using 2 accesses, namely Google Cendikia and ResearchGat. Findings – It Based on the results of a systematic literature review, the authors found 144 articles filtered using data inclusion criteria so a total of 33 data were obtained that were following the eligibility standards of 30 selected articles to be analyzed qualitatively descriptively. This research, shows that 17 literature has a positive and significant effect and dominates, 11 literature has a positive and & significant effect but does not dominate, and 2 literature has a negative and significant effect. Novelty/value – As employee performance has been an important factor in the human resource development last decades it is vital to understand how to retain employee performance. Keywords systematic literature review, work motivation, employee performance.